2001
DOI: 10.1080/003655201750163079
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus in Inflammatory Bowel Disease

Abstract: Staphylococcal superantigens are not involved in either the early lesions or the established lesions of Crohn disease. However, S. aureus infection occasionally may occur during the course of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
8
0
3
Order By: Relevance
“…Various studies have reported increased numbers of Staphylococcus spp. in the gut microbiota of active CD patients,5 8 which is similar in infants with inflammatory bowel disease (IBD)27 28 or allergy 29 30. This would suggest there is a relationship between this bacterial group and immune-mediated pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported increased numbers of Staphylococcus spp. in the gut microbiota of active CD patients,5 8 which is similar in infants with inflammatory bowel disease (IBD)27 28 or allergy 29 30. This would suggest there is a relationship between this bacterial group and immune-mediated pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal epithelial barrier dysfunction is postulated playing a role in etiology of IBD 48 . Bacteria and their product absorption via compromised epithelial barrier may play an important role in the pathogenesis of IBD or is a predisposing factor of IBD relapses 49 , 50 . Mast cells also play an important role in the pathogenesis of IBD 51 .…”
Section: Discussionmentioning
confidence: 99%
“…48 Bacteria and their product absorption via compromised epithelial barrier may play an important role in the pathogenesis of IBD or is a predisposing factor of IBD relapses. 49,50 Mast cells also play an important role in the pathogenesis of IBD. 51 Pretreatment with anti-tryptase, a key mediator of mast cell, can prevent experimental colitis.…”
Section: Pgn Activates Mast Cells To Compromise T84 Monolayer Barriermentioning
confidence: 99%
“…is anaerobic Gram-negative coccus of normal human flora that has rarely been identified as a pathogen [37]. Staphylococcus sp., pathogenic aerobic Gram-positive coccus, was isolated in some patients with rheumatoid arthritis [38] and in some studies was reported to be a superantigen in inflammatory bowel disease (IBD), particularly in Crohn's disease [39].…”
Section: Discussionmentioning
confidence: 99%